Pemanfaatan Barang Bekas Menjadi Barang Yang Bernilai Ekonomis Dari Pengelolahan Sampah Rumah Tangga Kota Martapura - Anestania; Eni Murdiati; Muzaiyanah (CV. ITTC INDONESIA, 2023)
This study discusses the use of used goods to become goods with economic value from household waste management in Martapura City. The purpose of this research is to find out how to use used goods to become goods of economic value to improve family welfare. 2) find out what are the supporting and inhibiting factors for the utilization of used goods into goods of economic value to improve family welfare. The method used in this research is a qualitative method with a descriptive approach. Data collection techniques used in this study through interviews, observation and documentation. Data analysis used in this study is through data reduction, presentation and inference. This is shown from the results of this study, 1) Utilization of Used Goods into Goods of Economic Value using the theory put forward by Davis, Dennis McQuali and Sven Windahl namely first, benefit is an expectation which is the same as Explor. Second, there is a position towards a deterministic view of mass media effects. Third, there is a long-standing desire to escape the tastes of the mass media. 2) Factors Supporting the Utilization of Used Goods into Goods of Economic Value in the City of Martapura. First, have a desire and will. Second, need. Then the inhibiting factors in the utilization of used goods into goods of economic value in the City of Martapura. First, the government does not intervene in helping the welfare of society. Second, there is no guidance or physical assistance. Business actors utilizing used goods must pay attention to the inhibiting factors in the utilization of used goods into goods of economic value, so that the businesses that have been built continue to grow rapidly in the wider community.